2020
DOI: 10.3390/plants9091177
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal Knowledge of Traditional Healers in Roi Et, Thailand

Abstract: Traditional healers in Thailand are a primary source of health care for the Thai people. Highly experienced traditional healers are generally older people and they continue to pass away without recording or passing on their knowledge. Consequently, the cumulative knowledge held by traditional healers regarding the use of medicinal plants is being eroded and could be lost. In this study, we aimed to identify and document the medicinal plants and associated ethnobotanical knowledge held by traditional healers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 50 publications
(89 reference statements)
7
41
1
Order By: Relevance
“…This forest is a collection of plants of which 69 species have been used by the community for medicinal purposes. The majority of plants were used for the treatment of gastrointestinal diseases such as abdominal pain and gastritis, similar to the results of studies by Pholhiamhan et al (2018) and Junsongduang et al (2020), where most plants were used for medicinal purposes to treat the gastrointestinal.…”
Section: Fidelity Level (%Fl)supporting
confidence: 63%
See 1 more Smart Citation
“…This forest is a collection of plants of which 69 species have been used by the community for medicinal purposes. The majority of plants were used for the treatment of gastrointestinal diseases such as abdominal pain and gastritis, similar to the results of studies by Pholhiamhan et al (2018) and Junsongduang et al (2020), where most plants were used for medicinal purposes to treat the gastrointestinal.…”
Section: Fidelity Level (%Fl)supporting
confidence: 63%
“…As reported in many studies, e.g. Chamratpan and Homchuen 2003, Inta et al 2008, Panyadee et al 2016, Saensouk et al 2016, Pholhiamhan et al 2018, Phumthum et al 2018, Junsongduang et al 2020 In several studies from many parts of the world, i.e. Umair et al 2017, Supiadi et al 2019, Jadid et al 2020, Rahman and Asha 2021, and Mutaqin et al 2020 Maha Sarakham is the province in Northeastern Thailand with the least forest area compared to the size of the province.…”
Section: Introductionmentioning
confidence: 87%
“…Thai culture assumes the traditional role of the man in a family as a leader and primary breadwinner, so men are expected to provide for their families [12]. The number of medicinal plant species known was not related to the healer's age and some herbalists treated only certain ailments such as cancer or postpartum conditions in women as already reported [12]. Herbalists who treat only certain conditions such as cancer, hemorrhoids, or muscular-skeletal disorders may have their knowledge from their parents.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the use of plants in indigenous communities is associated to biological, ecological, and socio-cultural factors, including production techniques and practices, religion, gender, and age [40][41]. Furthermore, Tai Lao healers also used animals and mineral substances for curing ailments, they practiced incantations and held ceremonies as part of the treatments as has also been reported among other cultures [12,38,42]. Medicinal knowledge of healers aims to heal not only physical illness, but also the mind and soul [40].…”
Section: Discussionmentioning
confidence: 99%
“…The study of medicinal plants is one of the methods to determine the relationships between cultural components of the environment and biological including examining the interaction (Bye 1986). There are various studies on ethnobotany and medicinal plants in Maha Sarakham Province and other places in Thailand such as Srithi (2009) reported the knowledge of medicinal plant and its erosion among the Mien (Yao) in northern, Saensouk et al (2016) studied diversity and uses of Zingiberaceae in Nam Nao National Park, Pholhiamhan et al (2018) reported the ethnobotany of Phu Thai Ethnic group in Nakhon Phanom Province, Junsongduang et al (2020) recognized ethnomedicinal knowledge of traditional healers in Roi Et Province, and Saensouk and Saensouk (2021) studied diversity, traditional uses, and conservation status of Zingiberaceae in Udon Thani Province.…”
Section: Introductionmentioning
confidence: 99%